Very low levels of direct additive genetic variance in fitness and fitness components in a red squirrel population - McFarlane, S. Eryn; Gorrell, Jamieson C.; Coltman, David W.; Humphries, Murray M.; Boutin, Stan; McAdam, Andrew G. (Ecology and Evolution, 2014)
A trait must genetically correlate with fitness in order to evolve in response to natural selection, but theory suggests that strong directional selection should erode additive genetic variance in fitness and limit future evolutionary potential. Balancing selection has been proposed as a mechanism that could maintain genetic variance if fitness components trade off with one another and has been invoked to account for empirical observations of higher levels of additive genetic variance in fitness components than would be expected from mutation– selection balance. Here, we used a long-term study of an individually marked population of North American red squirrels (Tamiasciurus hudsonicus) to look for evidence of (1) additive genetic variance in lifetime reproductive success and (2) fitness trade-offs between fitness components, such as male and female fitness or fitness in high- and low-resource environments. “Animal model” analyses of a multigenerational pedigree revealed modest maternal effects on fitness, but very low levels of additive genetic variance in lifetime reproductive success overall as well as fitness measures within each sex and environment. It therefore appears that there are very low levels of direct genetic variance in fitness and fitness components in red squirrels to facilitate contemporary adaptation in this population. This is an electronic version of an article that was originally published as: McFarlane, S.E., Gorrell, J.C., Coltman, D.W., Humphries, M.M., Boutin, S., & McAdam, A.G. (2014). Very low levels of direct additive genetic variance in fitness and fitness components in a red squirrel population. Ecology and Evolution, 4(10), 1729-1738. DOI:10.1002/ece3.982. Ecology and Evolution is an open access journal published by Wiley-Blackwell. More information about the journal can be found at: http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)2045-7758. This article can be accessed at: http://onlinelibrary.wiley.com/doi/10.1002/ece3.982/full. Ecology and Evolution Journal Cover Image (Volume 4, Issue 10) : A grizzly bear (Ursus arctos) of the Greater Yellowstone Ecosystem, which encompasses portions of Wyoming, Montana, and Idaho, USA. Photo by Ray Paunovick, Wild Planet Films, Bozeman, Montana, USA. https://viuspace.viu.ca/bitstream/handle/10613/3208/Gorrell.EE.pdf?sequence=4